Practical Implementation of the Concept of Health-Forming Technologies into the Process of Physical Education of Primary School Age Children - Kashuba, Vitalii; Goncharova, Nataliia; Butenko, Halyna (Journal of Education, Health and Sport, 2018)
The article considers the burning problem of positive influence of active tourism means on morbidity indices and degree of body resistance of primary school age children against unfavorable factors of the environment. The objective is to give a description of the morbidity of 1-4 grades students, to determine the degree of resistance of their organism to unfavorable factors of the environment and to determine the nature of the impact of active tourism means on these indices at primary school students in the process of physical education. The study consisted of ascertaining and educational experiments, which lasted one academic year each. 265 students of 1-4 grades took part in the ascertaining experiment. 91 students of 1, 3, 4 grades were involved in educational experiment and were divided into experimental and control groups.As a result of the ascertaining experiment, 55.09% of children with certain disorders in their health were identified, among which the diseases of the bone and muscular system predominate. It was established that the indices of the morbidity and degree of body resistance of children to unfavorable factors of the environment tend to deteriorate in the age dynamics. Children were characterized by low level of physical health. In order to determine the impact on these indices, the concept of health-forming technologies on the basis of active tourism means was developed. As a result of the educational experiment, it was established that children from experimental groups in comparison with children from control groups experienced a statistically significant improvement in the level of physical health, the degree of body resistance to unfavorable factors of the environment.